ADHERENCE TO METHADONE MAINTENANCE TREATMENT (MMT) AND ITS RELATED FACTORS IN WEST JAVA, INDONESIA (Proceedings of the International Conference on Public Health, 2019)
Adherence to Methadone Maintenance Treatment (MMT) is one of evaluation  criterias in MMT  because it requires a long period of  therapy. Adherence pattern and  related factors are important to achieve treatment goals. This study aimed to identify several factors related to MMT adherence in West Java, Indonesia. This cross-sectional study was carried out on 94 participants from  three selected primary health cares which conduct MMT program  in West Java in 2018. Data was collected  from patients interview,  methadone  retrieval  records from last 30 days, and  medical records. Analysis was performed using multivariate logistic regression. Participants in the age group 35-56 years were 83.7%, most of them were male (89.1%), and 65.2% were married. Total of  58.7% participants were adherent. Having history of  HIV positive [adjusted odd ratio (ORa) = 4.03; P = 0.005] and presence of  person who can share with (ORa = 6.26; P = 0.005) were significant related factors for higher adherence. Adherence to MMT was associated with several factors. To improve patient’s adherence, support from family and friends are  required. Meanwhile, patients with history of negative HIV must be monitored  to sustain patients’ adherence to MMT program.
Keywords: adherence, methadone, treatment, West Java